2011
DOI: 10.26522/brocked.v21i1.235
|View full text |Cite
|
Sign up to set email alerts
|

An Ethnography of Two Teachers’ Antiracist and Critical Multicultural Practices

Abstract: Educational theorists concerned with antiracist and critical multicultural practices have identified the need for teachers to begin changing the processes of social exclusion which children of colour experience in the school system. An ethnographic study of critical educators teaching practices is provided as a useful directive. The study examines how two critical educators respond to the diversity represented in their school by incorporating antiracist and critical multicultural approaches in their teaching p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…As Mogadime (2004) explains, "transformative pedagogy aims to redress the experience of marginality which students of colour experience in mainstream school curriculum which overlooks or undermines the histories of people of colour" (p. 1). In this way, transformative pedagogy brings the margins to the centre of the curriculum (Mogadime, 2011;Nieto, 2004) emphasizing an autobiographical curriculum (Pinar, 2004), thus facilitating the conceptualization and the development of culturally relevant critical discussions and didactic materials in TEPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Mogadime (2004) explains, "transformative pedagogy aims to redress the experience of marginality which students of colour experience in mainstream school curriculum which overlooks or undermines the histories of people of colour" (p. 1). In this way, transformative pedagogy brings the margins to the centre of the curriculum (Mogadime, 2011;Nieto, 2004) emphasizing an autobiographical curriculum (Pinar, 2004), thus facilitating the conceptualization and the development of culturally relevant critical discussions and didactic materials in TEPs.…”
Section: Resultsmentioning
confidence: 99%
“…Since personal identity, shaped by historical and societal realities, is fluid and malleable, it allows us to make sense of who we are, the places we come from, and our relationship with others (James & Shadd, 2001). As an individual's identity is in a continual process of construction and reconstruction, the impact of negotiating one's identity is a significant and sometimes, traumatic experience (Dwyer, 1999;Mogadime, 2011). For example, describing the collision of heterogeneous cultures, Bhabha (1994) used the term Third Space, as an in-between state of mind where an individual is in a "liminal state," between and betwixt two cultures, belonging to neither one nor the other.…”
Section: Recognizing and Respecting Multiple Cultural Identities In Cmentioning
confidence: 99%
“…Research regarding teachers' understandings and beliefs regarding equity and inclusion, in particular -why they choose to engage inequity work, is scant. Mogadime (2011) investigated the experiences of two critical educators, and how their identity informs their attempts to engage in antiracist and critical multicultural work in their schools, and found that the teachers' previous experiences and knowledge were highly informative for their equity practices. This study is therefore informed by the work of Mogadime (2011) as well as research on this topic in relation to the experiences of educational leaders as it is more developed (Griffiths, 2010;Singh, 2010;Theoharis, 2007).…”
Section: Why Do Equity Minded Teachers Do Equity Work?mentioning
confidence: 99%
“…Those who have researched this topic note that the lives of equity minded educators informs their practice, yet their voices of critical educators are unfortunately uncommon in existing literature and need to be uncovered (Mogadime, 2011(Mogadime, , 2012Mogadime & Smith, 2007). Researchers also note that many teachers unfortunately hold deficit conceptions of students, even those educators who claim to be engaging in equity and social justice work, and that this issue should be addressed in training and education (Sleeter et al, 2004); and that teacher candidates are often resistant to overcoming these deficit conceptions and adopting an equity lens to inform their practice (Brown, Wiggins, & Secord, 2009).…”
Section: Abstract: Teachers Motivations Equity Work Experiences Ofmentioning
confidence: 99%
“…Research regarding teachers' understandings and beliefs regarding equity and inclusion, in particular -why they choose to engage inequity work, is scant. Mogadime (2011) investigated the experiences of two critical educators, and how their identity informs their attempts to engage in antiracist and critical multicultural work in their schools, and found that the teachers' previous experiences and knowledge were highly informative for their equity practices. This study is therefore informed by the work of Mogadime (2011) as well as research on this topic in relation to the experiences of educational leaders as it is more developed (Griffiths, 2010;Singh, 2010;Theoharis, 2007).…”
Section: Why Do Equity Minded Teachers Do Equity Work?mentioning
confidence: 99%